Common Battlefield Training for Airmen - Manacapilli, Thomas (RAND Corporation, 2007)
Air Force members who do not routinely cross a defended perimeter when deployed may not have received sufficient training for doing so when they need to. The authors conducted surveys and interviews to determine the kinds of experiences airmen have had "outside the wire," worked with subject-matter experts to categorize them and suggest training levels, and developed a series of recommendations for course content and further areas for study.